Crystallization behaviour and growth kinetics of ZnTe in soda-lime-silica glass nanocomposites - Ersundu, M. Celikbilek (SOC GLASS TECHNOLOGY, 2019)
The crystallization behaviour and growth kinetics of ZnTe quantum dot-doped soda lime silica glass nanocomposites were investigated in this study. Glasses with the composition 70SiO(2)-18Na(2)O-10CaO-2Al(2)O(3)-0.5ZnTe (mol%) were prepared by the melt-quenching method and heat treated at 650 degrees C for different time periods from 0 to 120 h. The characterization of glass nanocomposites was realized using differential thermal analysis (DTA), x-ray diffraction (XRD), and high resolution scanning electron microscopy (HRSEM) techniques. Additionally, UV-Vis spectroscopy analysis was made and the optical band gap energy values were calculated. The band gap of glass nanocomposites showed a decrease from 3.55 to 3.40 eV by increasing heat treatment time at constant temperature. The time dependency of nanoparticle size was determined by growth kinetic studies and the size of nanoparticles was correlated with their quantum confinement behaviour. The size of the nanoparticles was found to lie between 25 to 60 nm with increasing time. Therefore, the glass nanocomposites synthesized in this study were found to show weak quantum confinement effect due to their larger crystal sizes than the Bohr exciton radius. Consequently, ZnTe quantum dot-doped soda-lime-silica glass nanocomposites show promise for various technologies such as lasers, optoelectronics, light emitting diodes, solar cells, sensors, etc, with their tuneable absorption edge within the visible region.
Keywords: QUANTUM DOTS; BAND-GAP; YB3+; Chemistry; Materials Science